Convergence Based Adaptation Management in Cosmopolitan Indonesia Magazine in an Effort to Sustain Business - Apresianti, Prita (MediaKom : Jurnal Ilmiah Komunikasi, 2025)
In the digital era, media convergence is crucial for media organizations to survive and compete with other media. The convergence process itself, which has become an obligation for conventional media, cannot just happen once but must be continuous, which means that media must continue to adapt, as done by Cosmopolitan management. This research was conducted to understand how Cosmopolitan Indonesia magazine carries out adaptation management based on convergence in an effort to maintain its business in 2024.This qualitative research uses a case study method, within a constructivist paradigm. To obtain primary data, semi-structured interview techniques were used with five informants who are the main decision-makers at Cosmopolitan Indonesia. In addition, observation was also conducted through digital media. As an analysis tool, the theories of Media Convergence, CMC, Change Management, POACE Analysis, and SWOT Analysis were used.To adapt to the digital age, Cosmopolitan Indonesia has implemented a convergence-based strategy. This involves leveraging digital technologies, such as social media, to engage a younger audience. The magazine has also focused on creating relevant content, collaborating with influencers, and integrating campaigns across platforms. However, challenges remain, including resistance to change among senior staff and limited resources. To overcome these obstacles, Cosmopolitan Indonesia has adopted a collaborative approach involving management, editorial, and business teams. Additionally, SWOT analysis is used to identify strengths, weaknesses, opportunities, and threats, helping to guide strategic decision-making.